2022
DOI: 10.1039/d2cp03390a
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of laser-induced ultrafast spin dynamics in trigonal monopyramidal iron and nickel complexes

Abstract: We present a first-principles study of the geometries, electronic structures, and laser-induced ultrafast spin dynamics in the four trigonal monopyramidal complexes [tpa$^{\text{t-Bu}}$Fe]$^-$, [tcma$^{\text{t-Bu}}$Fe]$^-$, [tpa$^{\text{t-Bu}}$Ni]$^-$, and [tcma$^{\text{t-Bu}}$Ni]$^-$ [tpa: tris-(pyrrolylmethyl)amine; tcma: tris(carbamoyl-methyl)amine;...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The laser-pulse parameters, namely incidence angles, amplitude, frequency, polarization, ellipticity, and chirp, are optimized with our own genetic algorithm [44]. Using such Λ-processes, the spin dynamics on numerous nanostructures, containing not only clusters [45][46][47] but also one-dimensional carbon chains [48][49][50] and 2D systems [51][52][53], has been successfully investigated and proven to be effective.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The laser-pulse parameters, namely incidence angles, amplitude, frequency, polarization, ellipticity, and chirp, are optimized with our own genetic algorithm [44]. Using such Λ-processes, the spin dynamics on numerous nanostructures, containing not only clusters [45][46][47] but also one-dimensional carbon chains [48][49][50] and 2D systems [51][52][53], has been successfully investigated and proven to be effective.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…SOC and B are added through perturbation theory (see eqn (1)). 81,82 The many-body states identified by the nonrelativistic computations are fundamentally mixed by the SOC and magnetic field. In fact, because direct excitations between states with opposite spin directions are not allowed within the electric-dipole approximation, spin-mixed intermediate states must be used as a bridge to transfer the population from the initial to the desired state.…”
Section: Computational Details and Methodsmentioning
confidence: 99%
“…They demonstrated that the combination of the charge transfer processes and the spin bifurcation on these systems can be achieved. 35 Zhang and co-workers 36,37 investigated the laser-induced ultrafast spin dynamics processes on rhombic graphene nanoflakes and proposed two-qubit logic gates. Liu et al showed magnetostraintronics in Co-coordinating fullerenes and established the strain-to-spin dynamics correlation by choosing different vibrational modes.…”
Section: Introductionmentioning
confidence: 99%